Large‐scale fluid‐deposited mineralization in Margaritifer Terra, Mars. Issue 13 (15th July 2017) - Thomas, Rebecca J.; Potter‐McIntyre, Sally L.; Hynek, Brian M.
Abstract: Mineral deposits precipitated from subsurface‐sourced fluids are a key astrobiological detection target on Mars, due to the long‐term viability of the subsurface as a habitat for life and the ability of precipitated minerals to preserve biosignatures. We report morphological and stratigraphic evidence for ridges along fractures in impact crater floors in Margaritifer Terra. Parallels with terrestrial analog environments and the regional context indicate that two observed ridge types are best explained by groundwater‐emplaced cementation in the shallow subsurface and higher‐temperature hydrothermal deposition at the surface, respectively. Both mechanisms have considerable astrobiological significance. Finally, we propose that morphologically similar ridges previously documented at the Mars 2020 landing site in NE Syrtis Major may have formed by similar mechanisms. Key Points: Structurally controlled mineral precipitation is reported at crater floor fractures in Margaritifer Terra, Mars Deposits are most consistent with a sedimentary genesis through subsurface cementation and subaerial hot spring precipitation Ridges have biosignature‐preservation potential, and this potential may also apply to similar ridges at the NE Syrtis Mars 2020 landing site Plain Language Summary: Minerals laid down by fluids from the subsurface are key locations where we may detect evidence for past life on Mars. This is because the subsurface is the longest‐term viable habitat on Mars and because these minerals can preserve biosignatures. We report evidence for ridges along fractures in and around craters in Margaritifer Terra. By drawing parallels with terrestrial analog environments and examining the regional context, we show that one type of ridge was most probably formed by deposition from groundwater and another type by hot or cold springs. Both types of site have considerable astrobiological significance and, indeed, so too may similar ridges at the Mars 2020 landing site in NE Syrtis Major, which may have formed in a similar way.